2004
DOI: 10.1111/j.1600-4469.2004.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of human periodontal ligament cells in media proposed for transport of avulsed teeth

Abstract: Many solutions have been examined as possible storage media for avulsed teeth. In this report, human periodontal ligament (PDL) cells were exposed for 1 h to culture medium, milk, Hanks Balanced Salt Solution (HBSS), Soft Wear, Opti Free, and Solo Care contact lens solutions, Gatorade, and tap water, at room temperature and on ice. The number of viable cells was counted using the trypan blue exclusion technique, immediately after exposure (0 h) and at 24 and 48 h, to test the proliferative capacity of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0
22

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(201 citation statements)
references
References 46 publications
8
171
0
22
Order By: Relevance
“…4 If the tooth cannot be replanted within five minutes it should be stored in a medium that will maintain vitality of periodontal ligament fibers. 2,5 It was encouraging to know that 59.8 % of the dentists chose Hank's balanced salt solution (HBSS) as the storage media for an avulsed tooth. Guidelines given by International Association for Dental Traumatology also suggests HBSS as storage media.…”
Section: Discussionmentioning
confidence: 99%
“…4 If the tooth cannot be replanted within five minutes it should be stored in a medium that will maintain vitality of periodontal ligament fibers. 2,5 It was encouraging to know that 59.8 % of the dentists chose Hank's balanced salt solution (HBSS) as the storage media for an avulsed tooth. Guidelines given by International Association for Dental Traumatology also suggests HBSS as storage media.…”
Section: Discussionmentioning
confidence: 99%
“…• Agua: La osmolalidad del agua varía de 3 -16 mOsm/Kg y su pH es de 7,41 4,20 es el medio de transporte menos adecuado pues al ser hipotónica desencadena la lisis celular, adicionalmente e l a l m a c e n a m i e n t o e n a g u a más de veinte minutos provoca grandes reabsorciones radiculares 14,20,23,25,27,29 • Saliva: Por tener una osmolalidad de 60 -80 mOsm/Kg y pH de 6,76 -7,35 [12][13][14][15][16]19,20 como por contener bacterias no es muy idónea. No obstante, los estudios demuestran que si el diente se pone en el vestíbulo bucal, los fibroblastos pueden mantenerse vitales unas dos horas.…”
Section: -28unclassified
“…El empleo de HBSS ha sido evaluado con éxito y siempre se suele utilizar como control positivo en estudios de medios de almacenamiento. 27 , Renu (BAUSCH AND LOMB) 30 , Titmus (CIBA-VISION) 30 , pero en general refieren que conservan las células del ligamento periodontal por períodos cortos de tiempo.…”
Section: -28unclassified
See 1 more Smart Citation
“…Although there has been some controversy (6,8), it has been suggested that milk with a lower fat content might be more appropriate to maintain PDLF viability than milk with a higher fat content (14). Previous studies indicate that cold milk is more effective than milk at room temperature (3,10,(15)(16)(17). Low temperatures have the advantage of reducing cellular metabolism (18) and limiting bacterial growth (3), which may affect the prognosis of tooth replantation.…”
Section: Introductionmentioning
confidence: 99%